A long-term case of rounded atelectasis with pneumothorax - Mizutani, Eiki; Morita, Riichiro (The Journal of the Japanese Association for Chest Surgery, 2010)
We report a rare case of rounded atelectasis with pneumothorax that persisted over a prolonged period. A 56-year-old female demonstrated pneumothorax and a mass measuring 3 cm in diameter in the right upper lung field on radiographic screening in 2004. She declined more detailed examinations, and was simply followed thereafter. Pneumothorax persisted, and the mass gradually enlarged. She subsequently agreed to undergo detailed examinations in September 2008. Bronchoscopy did not identify malignant findings histologically. We performed surgery because of persistent pneumothorax and the gradually enlarging mass. The visceral pleura showed wide pleural thickening, and the mass occupied about two-thirds of the right upper lobe. We performed a right upper lobectomy. Pathological examination showed extensive thickening of the pleura and rounded atelectasis without other primary pulmonary disease. She has been followed postoperatively without pneumothorax for five months to date.